2009
DOI: 10.1089/omi.2008.0031
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Taste and Its Influence on Food Selection

Abstract: Taste perception plays a key role in determining individual food preferences and dietary habits. Individual differences in bitter, sweet, umami, sour, or salty taste perception may influence dietary habits, affecting nutritional status and nutrition-related chronic disease risk. In addition to these traditional taste modalities there is growing evidence that "fat taste" may represent a sixth modality. Several taste receptors have been identified within taste cell membranes on the surface of the tongue, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(197 citation statements)
references
References 141 publications
6
182
1
8
Order By: Relevance
“…Previous reports have shown that the response to PROP was associated with increased bitterness and therefore reduced the liking for such vegetables as Brassicaceae (cruciferous) (27,32,47). The present participants, however, despite the apparent negative correlation for Brassicaceae vegetables, reported that the perceived PROP bitterness was not negatively correlated with the total vegetable intake (Tables 1 and 2).…”
Section: Discussioncontrasting
confidence: 66%
“…Previous reports have shown that the response to PROP was associated with increased bitterness and therefore reduced the liking for such vegetables as Brassicaceae (cruciferous) (27,32,47). The present participants, however, despite the apparent negative correlation for Brassicaceae vegetables, reported that the perceived PROP bitterness was not negatively correlated with the total vegetable intake (Tables 1 and 2).…”
Section: Discussioncontrasting
confidence: 66%
“…Family genetics then lead to taste sensitivities: for example, only some people inherit genes enabling taste of certain bitter compounds such as phenylthio-cabamide (PTC). Tasters of PTC have more food dislikes in general, including the taste of high fat foods (Garcia-Bailo et al 2009). There are heritable components in children's preferences for fruits and meats (Breen Plomin and Wardle 2006), and specific macronutrients, chiefly dietary fat (Reed et al 1997).…”
Section: Physiological Predispositionsmentioning
confidence: 99%
“…However, the sensory qualities of food are critical to food preference, and taste is the most important factor in the choice of food (GARCIA-BAILO et al, 2009).…”
Section: Sensory Resultsmentioning
confidence: 99%